Development and Validation of Sensitive GC and GC-MS Methods for the Detection and Quantification of Alkyl Mesylates in Pharmaceutical Active Ingredients - N Balaji; Sayeeda Sultana (Recent Developments in Chemistry and Biochemistry Research Vol. 6, 2024)
Methyl, ethyl, isopropyl, and hexyl mesylates were determined at trace levels in various active pharmaceutical ingredients by the capillary gas chromatographic method using flame ionization and mass spectrometers as detectors because of their mutagenic, carcinogenic, and teratogenic potential health risks in the medicines consumed by humans. A wide-bore gas chromatographic capillary column, the DB-WAX column (30 m × 0.53 mm × 1.0 \(μ\)m), was used for method development and validation. The carrier gas is helium for GC and GCMS methods with an injection volume of 4 \(μ\)L. Standard and sample solutions were prepared in a non-polar solvent such as n-hexane with the help of the solid-liquid extraction technique. The detection and quantitation limits were 0.02 and 0.05 ppm for methyl, ethyl, isopropyl, and hexyl mesylates for the GC and GCMS methods were achieved at very low levels by enhancing the analyte concentration up to 1 g quantity. The method was validated as per the procedures provided by the International Council for Harmonization of Technical Requirements for Pharmaceuticals for Human Use (ICH) and the Food and Drug Administration (FDA) of the United States of America. The %RSD for methyl, ethyl, isopropyl, and hexyl mesylates were less than 2.5%. The linearity of the method was demonstrated from 0.02 ppm to 5 ppm with respect to the analyte concentration, and it afforded correlation coefficients exceeding 0.99. The recoveries of methyl mesylate, ethyl mesylate, isopropyl mesylate, and hexyl mesylate were in the range of 97.1 to 107.1%. Hence, this is a robust method for the determination of alkyl mesylates in these APIs. Also, this method has been verified by a gas chromatograph equipped with mass spectrometry (GC-MS) for the detection of alkyl mesylates.